Leadership Styles of Deans/heads and Employees’ Workplace well-being of Divine Word Colleges in Ilocos Region, Philippines - Abun, Damianus; Egdonna A. Quinto,; Theogenia Magallanes,; Mary Joy Encarnacion,; Nathanael Flores, (Technium Social Sciences Journal, 2020)
The study wanted to determine the correlation between leadership styles of deans/heads and employees’ workplace well-being. To support the theory of the study, the related literature was reviewed. The population of the study was the employees and the heads of Divine Word Colleges in the Ilocos Region. The study applied the correlational research design and the data were gathered using questionnaires. It used the descriptive and inferential statistics to interpret the data and weighted mean was used to determine the level of leadership styles and workplace well-being and Pearson r Product moment of Correlation was used to determine the correlation between the variables. The study found that the four leadership styles of deans were at a moderate level and there is a correlation between leadership styles of deans/head and the workplace well-being of employees. Therefore the hypothesis of the study is accepted